The Effect of Economic Conditions, Family Environment and Self-Efficacy on Entrepreneurial Interests of Economics Department Students at Mataram University - Iwan Putra; St. Maryam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the influence of economic conditions, family environment, and self-efficacy on entrepreneurial interest among students of the Economics Department at the University of Mataram. The research employs a quantitative approach using multiple linear regression analysis. A total of 50 students were selected through proportional stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed with SPSS software. The results indicate that both simultaneously and partially, all three independent variables—economic conditions, family environment, and self-efficacy—have a positive and significant effect on entrepreneurial interest. The R² value of 0.559 shows that 55.9% of the variation in entrepreneurial interest can be explained by these variables. These findings suggest that a combination of external support and personal confidence plays a crucial role in fostering students' entrepreneurial motivation.